Soil macronutrient status in different depths after wheat harvest in the paddy-wheat cropping system of Rupandehi District of Nepal - Amgain, Rita; Khadka, Dinesh; Joshi, Sushila (Nepal Agriculture Research Journal, 2023)
Understanding the soil nutrient content varied with the soil depth is one of the most important aspects of every crop husbandry practice and information about the soil nutrient status of a certain area is very important for nutrient management programs. Considering this, a study was carried out in order to find out the depth-wise status of soil pH, soil organic matter and macronutrients in the paddy-wheat cropping system of the different areas of Rupandehi District of Nepal. The study was undertaken from April, 2019 to May 2019 immediately after the harvesting of the wheat crop. Altogether 108 samples were collected from two soil depths (0-10 cm and 10-20 cm) of randomly selected 54 sampling points by using a soil sampling auger. The soil parameters were determined by analyzing the samples at National Soil Science Research Centre, Khumaltar. The results of the study showed that soil pH values ranged from 6.73 to 8.03, but were non-significantly (p>0.05) affected soil depth. The soil organic matter, Total Nitrogen (N), available phosphorus (P2O5) and available potassium (K2O) in the soil were significantly (p>0.05) affected by soil depth. Higher soil organic matter (2.01±0.06%), Total N (0.10±0.002%), available P2O5 (25.56±1.33 mg kg-1) and available K2O (47.9± 2.11 mg kg-1) were found in 0-10 cm soil depth. Higher concentrations of nutrients in the upper surface may be due to the incorporation of crop residue and supplementation of depleted nutrients by external sources of fertilizers.